Estimating the global costs of Vitamin A capsule supplementation: A review of the literature - Neidecker-Gonzales, Oscar; Nestel, Penelope; Bouis, Howarth E. (SAGE Publications, 2007)
Background. Vitamin A supplementation reduces child mortality. It is estimated that 500 million vitamin A capsules are distributed annually. Policy recommendations have assumed that the supplementation programs offer a proven technology at a relatively low cost of around US$0.10 per capsule. Objectives. To review data on costs of vitamin A supplementation to analyze the key factors that determine program costs, and to attempt to model these costs as a function of per capita income figures. Methods. Using data from detailed cost studies in seven countries, this study generated comparable cost categories for analysis, and then used the correlation between national incomes and wage rates to postulate a simple model where costs of vitamin A supplementation are regressed on per capita incomes. Results. Costs vary substantially by country and depend principally on the cost of labor, which is highly correlated with per capita income. Two other factors driving costs are whether the program is implemented in conjunction with other health programs, such as National Immunization Days (which lowers costs), and coverage in rural areas (which increases costs). Labor accounts for 70% of total costs, both for paid staff and for volunteers, while the capsules account for less than 5%. Marketing, training, and administration account for the remaining 25%. Conclusions. Total costs are lowest (roughly US$0.50 per capsule) in Africa, where wages and incomes are lowest, US$1 in developing countries in Asia, and US$1.50 in Latin America. Overall, this study derives a much higher global estimate of costs of around US$1 per capsule.